The Principle of Sufficient Reason and Free Will - McAllister, Blake (Stance: an international undergraduate philosophy journal, 2019)
I examine Leibniz’s version of the Principle of Sufficient Reason with respect to free will, paying particular attention to Peter van Inwagen’s argument that this principle leads to determinism. Ultimately I conclude that Leibniz’s formulation is incompatible with free will. I then discuss a reformulation of the Principle of Sufficient Reason endorsed by Alexander Pruss that, I argue, manages to both retain the strength of Leibniz’s formulation and remain consistent with free will.